The Early Emergence of Temporal Reference in Mother-Child Multimodal Communication (2014)
ABSTARCT: The study longitudinally explores the early emergence of temporal reference to objects/events that are either present or absent in time while mothers and children use and combine pointing and verbal references. Over one year of observations and in five separate sessions, eight Spanish mothers and their one- and two-year-old babies were observed while performing daily routines at home. The results indicated that overall mothers and children used more verbs referring to the present frame than to the past and future frames. As compared with the production of utterances accompanied by pointing, children were more likely to produce present references in the young group and displaced references (mostly near past and near future) in the older group when utterances were produced without pointing. Mothers closely preceded or accompanied the children’s verbal and gestural referential production to either immediate or displaced referents across ages, indicating that they systematically engage their children in talking about the present and especially about the future.